Precipitation scaling with temperature in warm and cold climates: An analysis of CMIP5 simulations. Issue 15 (2nd August 2013) - Li, Guangqi; Harrison, Sandy P.; Bartlein, Patrick J.; Izumi, Kenji; Colin Prentice, I.
Abstract: [1] We investigate the scaling between precipitation and temperature changes in warm and cold climates using six models that have simulated the response to both increased CO2 and Last Glacial Maximum (LGM) boundary conditions. Globally, precipitation increases in warm climates and decreases in cold climates by between 1.5%/°C and 3%/°C. Precipitation sensitivity to temperature changes is lower over the land than over the ocean and lower over the tropical land than over the extratropical land, reflecting the constraint of water availability. The wet tropics get wetter in warm climates and drier in cold climates, but the changes in dry areas differ among models. Seasonal changes of tropical precipitation in a warmer world also reflect this "rich get richer" syndrome. Precipitation seasonality is decreased in the cold‐climate state. The simulated changes in precipitation per degree temperature change are comparable to the observed changes in both the historical period and the LGM. Key Points: Energy supply for evaporation limits precipitation scaling with temperature Water limitations reduce modeled precipitation scaling on land by a quarter Simulated changes are comparable to observed LGM and historical changes